O projeto especial multinacional de educação – Brasil – Paraguai - Uruguai e a concepção da escola pública na região oeste do Paraná: 1975 a 1983 - Mufatto, Lidiane Maciel (2016)
This dissertation aims to analyze the Project Multinational Education Brazil-Paraguay-Uruguay - OAS (1975-1983). It discusses the context in which the document was prepared, the factors that determined its presence in western of Parana state and the conception of education in that time. We will take into account the hegemonic forces and against hegemonic who worked in the dynamics of your execution and the demands for schooling of local and regional society. It also analyzes the relationship between state, society and education, considering investments in the area to advance the market. The methodology involved in this work, understands the importance of the historical context of its production from bibliographical references and primary and secondary sources covering the social, cultural, economic and political elements. We aim to examine the genesis and implementation of the MEC Project. The research intend to mainly discuss the design of public school in this exposed documents with the social demands of western Paraná state region with the historical context surrounding the national and international level of the project. As one of our conclusion elements, we understand that the concept of public education in western Paraná is evident in the course of conduct of the MEC/OAS Project, carrying out studies and analyzes of the history of the region, its performance was simultaneously with the political relations, social and educational. As one of the factors that the Project focused, an action as a contribution is the origin of the Western Parana State University (UNIOESTE), which is characterized as a multicampi university. Precisely because of these activities, with the implementation of higher education courses in both was focused by the Project on training of human resources, the region has been mobilized for its development. With the organization and planning of their activities sought to achieve with its educational investment in virtually the entire region.